2011
DOI: 10.1007/s11069-011-9992-4
|View full text |Cite
|
Sign up to set email alerts
|

Why do people not learn from flood disasters? Evidence from Vietnam’s northwestern mountains

Abstract: This article explores how the causes and impacts of a flood event as perceived by local people shape immediate responses and future mitigation efforts in mountainous northwest Vietnam. Local flood perception is contrasted with scientific perspectives to determine whether a singular flood event will trigger adjustments in mitigation strategies in an otherwise rarely flood-affected area. We present findings from interdisciplinary research drawing on both socioeconomic and biophysical data. Evidence suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 32 publications
(32 reference statements)
1
47
0
3
Order By: Relevance
“…Brody et al (2009) point toward improvements in local flood mitigation policies after historical flood events in Florida. Conversely, very little beneficial learning seems to take place where disasters are rare events (Schad et al, 2012) or happen only at the very local level (Voss and Wagner, 2010).…”
Section: Beneficial Learning From Natural Disastersmentioning
confidence: 99%
“…Brody et al (2009) point toward improvements in local flood mitigation policies after historical flood events in Florida. Conversely, very little beneficial learning seems to take place where disasters are rare events (Schad et al, 2012) or happen only at the very local level (Voss and Wagner, 2010).…”
Section: Beneficial Learning From Natural Disastersmentioning
confidence: 99%
“…In order to avoid the negative effects of eroded particles coming from surrounding upland fields and pesticides from neighboring paddy fields, our study ponds, using the modified management system, were isolated from external water flows. The dikes used needed to be strengthened against flooding caused by heavy rains (Schad et al 2012), and cracks and macro pores in the dikes had to be sealed. Ponds were equipped with proper pipes for controlling inflows and outflows, with the outlet pipe situated at the deepest point in the pond so that the water could be completely drained for harvests and drying purposes.…”
Section: Implementation Of the Modified Pond Management Systemmentioning
confidence: 99%
“…Each household usually cultivates one to several paddy rice fields and at least one fish pond. Detailed information about the study area can be found in Lamers et al ., Schad et al . and Anyusheva et al …”
Section: Methodsmentioning
confidence: 99%